Gallbladder Burkitt's Lymphoma: A Literature Review Including a Case Report in a Child Living with HIV - Nathalia Lopez Duarte; Ana Paula Silva Bueno; Bárbara Sarni Sanches; Gabriella Alves Ramos; Layanara Albino Batista; Thalita Fernandes de Abreu; Marcelo Gerardin Poirot Land; Cristiane Bedran Milito (MDPI AG, 2024)
Malignant lymphoma is an unusual form of gallbladder neoplasm. Almost all these tumors are diffuse large B-cell lymphomas or mucosa-associated lymphoid tissue-type lymphomas. Herein, we present a literature review of gallbladder Burkitt's lymphoma (BL) cases that includes also an unpublished case in an HIV-infected child, observed by our center. The patient (a five-year-old black female child) attended the Federal Hospital of Lagoa, Rio de Janeiro, Brazil, underwent cholecystectomy, and the postoperative pathological analysis of the gallbladder revealed a diagnosis of BL (EBV-positive). Also, HIV serology was performed and returned positive. She was transferred to the Martagão Gesteira Institute of Pediatrics and Childcare for oncological treatment, dying from sepsis and disease progression about 18 months later. The patient did not undergo ART/cART. Previous cases of gallbladder BL were herein described and analyzed to characterize the clinicopathological features and possible similarities. BL can occur in the gallbladder both in the context of HIV infection and in the pediatric population. A biopsy is mandatory in cases with suggestive findings of lymphoma, and an early diagnosis can change the course of the disease. Furthermore, the case highlights the importance of an early initiation of ART/cART in people living with HIV (PLWH), especially in children.